Using Current Reality Tree to Analyse The Root Cause of Problem: A Case Study in PT Yumida Siba Utama - Hidayati, Melati Rakhmah; Adhiutama, Akbar (Journal of Business and Management, 2013)
Nowadays, SMEs in Indoesia run into the good development and lead to better economy’s Indonesia. One of them is SME of motorcycle parts manufacturing. This paper aims to know what the root cause of problems that occur at SME of motorcycle parts manufacturing in PT Yumida Siba Utama. Open interview was used to know the current condition of company. Creating value stream mapping and check sheet were obtained by observation to plant. Data collection was taken from company and diveded into primary data and secondary data. Current Reality Tree was utilized to identify the root cause of problems. By using methodology mentioned above, the researcher found the root cause of problems which occurs. According to Current Reality Tree tool, the root cause of problems that occurs is the company doesn’t enforce the employees especially HR and operators to understand SOP. The construct of current reality tree design developed in this study reveals the existing condition and symtpoms. Therefore, this study can be viewed as an attempt to increase the level of awareness on problems that occurs at SME. Keywords: current reality tree, SME, manufacturing---------------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.